Tailored frequency-escalated primary prophylaxis for severe haemophilia A: results of the 16-year Canadian Hemophilia Prophylaxis Study longitudinal cohort. Issue 6 (June 2018) - Feldman, Brian M; Rivard, Georges E; Babyn, Paul; Wu, John K M; Steele, MacGregor; Poon, Man-Chiu; Card, Robert T; Israels, Sara J; Laferriere, Nicole; Gill, Kulwant; Chan, Anthony K; Carcao, Manuel; et al.
Summary: Background: Severe haemophilia A has high morbidity, and treatment, while effective, is very expensive. We report the 16-year follow-up of the Canadian Hemophilia Prophylaxis Study, which examined the effectiveness of tailored frequency-escalated primary prophylaxis with a focus on health outcomes within the domains of body structures and functions, and activities and participation (according to the WHO International Classification of Functioning, Disability and Health [WHO-ICF] framework) and a view to reducing consumption of costly clotting factor, which accounts for more than 90% of the cost of care of severe haemophilia. Methods: In this longitudinal study, boys with severe haemophilia A from 12 Canadian centres were enrolled at age 1·0–2·5 years. They were treated with standard half-life recombinant factor VIII (SHL-rFVIII), beginning as once-weekly prophylaxis with 50 IU/kg and escalating in frequency (with accompanying dose adjustments) in response to breakthrough bleeding as determined by the protocol. The primary endpoint for this analysis was joint health, as measured by the modified Colorado Child Physical Examination Scores (CCPES) at study end. All analyses were done by intention to treat. The trial is complete, and is registered with ClinicalTrials.gov, number NCT01085344 . Findings: Between June 26, 1997, and Jan 30, 2007, 56 boys were enrolled. They were followed for a median of 10·2 years (to a maximum of 16·1 years). Median rFVIII usage was about 3600 IU/kg per year. The median end-of-study CCPES physical examination score was 1 (IQR 1–3; range 0–12) for the left ankle and 1 (1–2; 0–12) for the right ankle, with all other joints having a median score of 0. No treatment-related safety events occurred over the duration of the study, including central venous catheter infections. The median annualised index joint bleeding rate was 0·95 per year (IQR 0·44–1·35; range 0·00–13·43), but 17 (30%) patients had protocol-defined unacceptable breakthrough bleeding at some point during the study. Interpretation: Tailored frequency-escalated prophylaxis leads to very little arthropathy and very good health outcomes within the WHO-ICF domains, and only uses a moderate amount of expensive clotting factor as compared with standard prophylaxis protocols. Some sequelae of bleeding were observed in our cohort, and future studies should consider a more stringent protocol of escalation. Funding: This study was initially funded by grants from the Medical Research Council of Canada/Pharmaceutical Manufacturers Association of Canada Partnership Fund and the Bayer/Canadian Blood Services/Hema-Quebec Partnership Fund. Subsequent renewals were funded by Bayer.